Pengaruh padat penebaran terhadap kelangsungan hidup larva ikan Betok (Anabas testudineus) yang dipelihara dalam baskom - Nyata Susila (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The purpose of this study was to determine optimal stocking density of Climbing perch larvae were reared in container. This study used Completely Randomized Design (CRD) with 3 treatments and 3 replications that was stocking density 10 larva/L (A), 20 larva /L (B), and 30 larva /L (C). The observed parameters were the survival of the Climbing perch larvae and water quality include water temperature, DO (dissolved oxygen), and pH. The results showed the highest survival rate in treatment A in the amount of 55%, followed by treatment B 45.8%, and the lowest by treatment C 38%. Water quality parameter were in the tolerance range of Climbing perch larvae with temperature 27.1 – 27.0OC, DO (dissolved oxygen) 3.8 - 5.3 mg / L and pH 4.6 – 6.6. Key words : Stocking density, survival rate, Anabas testudineus larvae.